PENGARUH LATIHAN VARIASI BOLA TERHADAP KETERAMPILAN SEPAK SILA PESERTA EKSTRAKURIKULER SEPAK TAKRAW DI SDN 112/I PERUMNAS MUARA BULIAN - Jeffry Trinando; Ugi Nugraha (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
One of the good training methods is by varying the ball used during training which can affect sepak takraw skills. This study aims to determine the effect of ball variation training on improving sepak takraw skills. The research conducted is an experimental study, which is conducted to determine whether or not there is an increase in something imposed on the sample to be studied. This experimental study was conducted at SDN 112/I Perumnas Muara Bulian with 23 people, with details of an initial test, namely a test conducted before doing ball variation training and a final test, namely a test after doing sepak takraw ball variation training. The overall results of the initial sepak takraw skill test score were 350 with an average sepak takraw skill score of 15.21. While the overall results of the final score on the sepak takraw skill test were 500 with an average sepak takraw skill score of 21.73. Based on the results of this study, it can be concluded that a person who does ball variation training will have 6.52 more advanced sepak takraw skill results than someone who does not do sepak takraw ball variation training. The results of the study indicate that the hypothesis proposed is there is a significant influence of ball variation training on improving sepak takraw skills accepted with a 95% confidence level which can be seen from the results of the t-test, namely the Significant value=0.00 is smaller than the value of α=0.05. So it can be concluded that ball variation training can improve sepak takraw skills by 6.52%.